Using glucosamine to improve the properties of photocrosslinked gelatin scaffolds. (February 2015) - Suo, Hairui; Xu, Kedi; Zheng, Xiaoxiang
The use of hydrogel-based cell transport scaffolds holds great promise in regenerative medicine, such as treating osteoarthritis. Gelatin and glucosamine are the ideal materials to be used in the hydrogel scaffolds for cartilage regeneration for they could act as compositions of cartilage. To overcome the weak strength of traditional gelatin hydrogels and down-regulate cell toxicity of glucosamine, gelatin and glucosamine molecules were grafted with acrylate groups and covalently crosslinked under photo-radiation to form hydrogels. Hydrogels with tuning physiochemical properties were produced according to different proportions of methacrylate gelatin (GelMA) and N-acryloyl glucosamine (AGA). The process of photocrosslinking was elaborated, and the hypothesis of increasing AGA concentration leading to higher strength of hydrogels was corroborated by testing rheological property and scanning micro-morphological features. A serial of properties, including smaller swelling ratio, lower gelatin dissolution and slower degradation of GelMA/AGA hydrogels with higher AGA concentration further proved our hypothesis. Moreover, AGA molecules showed less cytotoxicity than unmodified glucosamine molecules and the incorporation of AGA molecules in GelMA/AGA hydrogels upregulated cell adhesion and spreading on the hydrogel surface. All of these results indicated that addition of AGA molecules could significantly alter the physiochemical properties of GelMA/AGA hydrogels, which may have broad application prospects in the future.